Antistatic nylon material and preparation method thereof
By using SiO2 seed-induced nanopolyacrylamide in nylon materials, combined with other additives, the problem of insufficient mechanical properties of existing antistatic nylon materials is solved, and the antistatic and mechanical properties of the material is achieved.
Patent Information
- Application Number
- CN202510008938.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While improving antistatic properties, existing antistatic nylon materials sacrifice the mechanical properties of the material and limit their processing applications.
Nanopolyacrylamide is used as a component to prepare nanoscale polyacrylamide by SiO2 seed as nuclear induction, and antistatic nylon materials are prepared in combination with nylon, antistatic agent, flame retardant, antioxidant, coupling agent and stabilizer.
The good antistatic and mechanical properties of the material are achieved. The good compatibility and dispersion of nanopolyacrylamide enables the components to fully exert their performance, and SiO2 effectively increases the toughness and heat resistance of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nylon materials, and in particular to an antistatic nylon material and a preparation method thereof. Background Art
[0002] Nylon is a plastic material with excellent comprehensive properties, which is used in various mechanical and electrical parts such as bearings, gears, pulley pump impellers, blades, high-pressure seals, gaskets, valve seats, battery boxes, electrical coils, and cable connectors. However, in practice, most nylon products will generate static electricity, and static discharge will break down integrated circuits, causing integrated circuit failures. Therefore, using antistatic materials can prevent static electricity from damaging microelectronic circuits.
[0003] The methods of antistatic plastics mainly include surface treatment and mixing. Most of them are to increase the antistatic performance by adding different antistatic components. The most widely used method is to add conductive fillers to prepare composite materials. Carbon black system, metal and metal oxide system are more commonly used for conductive fillers. However, the compatibility of the three fillers with polymer matrix is poor, and more addition is required to achieve the effect, which usually affects the performance of the material. In the prior art, CN 111138847 A discloses a mixed antistatic semi-aromatic nylon resin and a preparation method thereof, which is an ion conductive antistatic nylon composed of semi-aromatic nylon, polyacrylamide (PAM), inorganic salts and other components. The ion transmission capacity is provided by polymer and inorganic salts, and a permanent antistatic semi-aromatic nylon composite material with both ion hybrid conductive antistatic performance and compatibility is prepared. Although the material has achieved good antistatic performance, the material sacrifices the mechanical properties of the material, which limits the processing application of the material.
[0004] Based on this, the present application proposes a nylon composite material having both antistatic and good mechanical properties to solve the above problems. Summary of the invention
[0005] In order to overcome the above disadvantages, the present application provides an antistatic nylon material and a preparation method thereof, an antistatic nylon material, the components of which are measured by weight, including 70-85 parts of nylon, 10-20 parts of nano-polyacrylamide, 5-10 parts of antistatic agent, 10-15 parts of flame retardant; 1-2 parts of antioxidant, 1-2 parts of coupling agent, and 1-2 parts of stabilizer;
[0006] Further, the antistatic agent is carbon black;
[0007] Furthermore, the stabilizer is any one of erucamide and calcium stearate.
[0008] Further, the antioxidant is any one of antioxidant 1010, antioxidant 1098 and antioxidant 168;
[0009] Furthermore, the flame retardant is magnesium hydroxide;
[0010] Furthermore, the coupling agent is silane coupling agent KH-550 or KH-560;
[0011] Furthermore, the nano-polyacrylamide is nano-polyacrylamide prepared by using SiO2 crystal seeds as core induction.
[0012] Furthermore, the preparation method of the nano-polyacrylamide is:
[0013] S1, mixing fluorosilicic acid and ammonia water, and aging to obtain SiO2 seed solution;
[0014] S2, dissolving the polymerization monomer and the surfactant in the seed solution obtained in step S1, and then adding an initiator to initiate a polymerization reaction to obtain a polymer aqueous solution;
[0015] S3, adding a crystallizing agent to the polymer aqueous solution obtained in S2, the polymer is precipitated, the solid-liquid is separated, and the obtained solid is washed and dried to obtain nano-polyacrylamide.
[0016] Furthermore, in step S1, the concentration of fluorosilicic acid is 3-10wt%, the concentration of ammonia water is 2-10%, the pH of the mixing endpoint is controlled at 6-7, and the aging time is generally 1 to 12 hours. After aging, a stable SiO2 seed solution is obtained, and the SiO2 seeds are uniformly distributed in the solution in the form of nanoparticles.
[0017] Furthermore, in step S2, the polymerizable monomer is selected from two or more of acrylamide, methacrylamide, N-isopropylacrylamide, and acrylic acid, and a polymerization reaction occurs under the conditions of an initiator and heating to generate polyacrylamide. The initiator is a redox initiator selected from at least one of potassium persulfate, ammonium persulfate, sodium perbromide, and hydrogen peroxide.
[0018] Further, the concentration ratio of the polymer product to the seed crystal in S2 is 20-150:1;
[0019] In the step S2, the surfactant is preferably a sulfonic acid surfactant, and the surfactant keeps the charge uniformly distributed in the system to avoid the rapid polymerization of the polymerization product into large particles. The polymerization reaction lasts for 6-18h, and the polymerization product is wrapped around the SiO2 seed crystals to maintain a stable uniform distribution state. After the crystallization agent is added to the above-mentioned stable system, the solubility of the polymerization product in the solution is rapidly reduced, and the polymerization product is gradually condensed and precipitated with SiO2 seed crystals as the core. In order to control the particle size of the precipitated product, the ratio of the polymerization product to the seed crystal concentration must be controlled. If the former concentration is too high, the particle size of the precipitated product is too large. If the former concentration is too small, the production efficiency is reduced. The weight concentration ratio of the two is preferably 20-150:1.
[0020] Preferably, the amount of the crystallizing agent is 10-60% of the total weight of the water in step S1, and the crystallizing agent is an organic solvent that is soluble in water but does not dissolve the polymer product, preferably at least one of methanol, ethanol and acetone.
[0021] Preferably, the amount of surfactant used is 0.1-2% by weight of the polymerized monomers, and the amount of initiator used is 1-3% by weight of the polymerized monomers.
[0022] Furthermore, the present application provides a method for preparing an antistatic nylon material, wherein nylon, nano-polyacrylamide, antistatic agent, flame retardant, antioxidant, coupling agent, and stabilizer are put into a mixer for mixing, and extruded and granulated in a twin-screw extruder, with a feeding section of 230 to 250°C, a compression section of 260 to 270°C, a homogenization section of 265 to 270°C, and a die of 270 to 275°C; the extrusion speed is 245r / min, and the feeding speed is 14r / min. Injection molding process conditions: feeding section 255°C, middle section 270°C, and gate 270°C.
[0023] The beneficial effects of the present invention are:
[0024] The components of the present invention are added with nano-polyacrylamide, which has good compatibility and dispersibility to improve the antistatic and mechanical properties of the material. The nano-polyacrylamide is prepared by induction with SiO2 seed crystals as the core, the raw materials are cheap and easy to obtain, the process is simple, the obtained product is a nano-particle size, uniformly dispersed nano-particle size polyacrylamide, has good compatibility and dispersibility, can make the components fully exert their performance, only a small amount of carbon black components is needed to achieve a good antistatic effect; at the same time, it can effectively increase the mechanical properties of the material; SiO2 in the nano-polyacrylamide plays a role in strengthening and toughening, improving heat resistance, improving mechanical properties, and the nylon plastic product obtained with good dispersibility has uniform quality. DETAILED DESCRIPTION
[0025] Example 1
[0026] An antistatic nylon material comprises, by mass, 80 parts of nylon 66, 15 parts of nano-polyacrylamide, 8 parts of antistatic agent, 12 parts of flame retardant, 2 parts of antioxidant, 2 parts of coupling agent and 1 part of stabilizer; wherein the antistatic agent is carbon black; the stabilizer is calcium stearate; the antioxidant is antioxidant 1098; the flame retardant is magnesium hydroxide; the coupling agent is silane coupling agent KH-560; the nano-polyacrylamide is a nano-polyacrylamide prepared by SiO2 crystal seed as core induction.
[0027] The preparation method of nano polyacrylamide is as follows:
[0028] S1, 10wt% fluorosilicic acid and 2wt% ammonia water were mixed, the end point pH value was controlled at 6.5, and aged for 1h to obtain 100g of a solution with a SiO2 concentration of 5wt%;
[0029] S2, dissolving 65 g of acrylamide, 5 g of acrylic acid and 0.35 g of sodium dodecyl sulfate in the seed solution obtained in step S1, and then adding 0.84 g of ammonium persulfate to carry out polymerization reaction to obtain a polymer aqueous solution;
[0030] S3, add 10g of methanol to the polymer aqueous solution obtained in S2, slowly stir, the polymer gradually precipitates, separate the solid and the liquid, wash and dry the obtained solid to obtain 63g of nano-polyacrylamide.
[0031] Example 2
[0032] An antistatic nylon material comprises, by mass, 80 parts of nylon 66, 15 parts of nano-polyacrylamide, 8 parts of antistatic agent, 12 parts of flame retardant, 2 parts of antioxidant, 2 parts of coupling agent, and 1 part of stabilizer; wherein the antistatic agent is carbon black; the stabilizer is erucamide; the antioxidant is antioxidant 1010; the flame retardant is magnesium hydroxide; and the coupling agent is silane coupling agent KH-550.
[0033] The preparation method of nano polyacrylamide is as follows:
[0034] S1, 3wt% fluorosilicic acid and 10wt% ammonia water were mixed, the end point pH value was controlled at 7, and aged for 10h to obtain 100g of a solution with a SiO2 concentration of 8.6wt%;
[0035] S2, dissolving 32 g of acrylamide, 3 g of methacrylamide and 0.5 g of sodium α-olefin sulfonate in the seed solution obtained in step S1, and then adding 0.9 g of potassium persulfate to carry out polymerization reaction to obtain a polymer aqueous solution;
[0036] S3, add 50g of ethanol to the polymer aqueous solution obtained in S2, slowly stir, the polymer gradually precipitates, separate the solid and the liquid, wash and dry the obtained solid to obtain 34g of nano-polyacrylamide.
[0037] Example 3
[0038] An antistatic nylon material comprises, by mass, 80 parts of nylon 66, 15 parts of common polyacrylamide, 8 parts of antistatic agent, 12 parts of flame retardant, 2 parts of antioxidant, 2 parts of coupling agent and 1 part of stabilizer; wherein the antistatic agent is carbon black; the stabilizer is calcium stearate; the antioxidant is antioxidant 1098; the flame retardant is magnesium hydroxide; and the coupling agent is silane coupling agent KH-560.
[0039] The preparation method of ordinary polyacrylamide is a polymerization preparation method without adding SiO2 seed crystals as nucleus induction, and the reaction conditions and parameters of the specific reactants are the same as those in Example 1.
[0040] Example 4
[0041] An antistatic nylon material includes, by mass, 80 parts of nylon 66, 8 parts of antistatic agent, 12 parts of flame retardant, 2 parts of antioxidant, 2 parts of coupling agent, and 1 part of stabilizer; wherein the antistatic agent is carbon black; the stabilizer is calcium stearate; the antioxidant is antioxidant 1098; the flame retardant is magnesium hydroxide; and the coupling agent is silane coupling agent KH-560. It does not contain ordinary polyacrylamide.
[0042] Example 5
[0043] An antistatic nylon material includes, by mass, 80 parts of nylon 66, 20 parts of antistatic agent, 12 parts of flame retardant, 2 parts of antioxidant, 2 parts of coupling agent, and 1 part of stabilizer; wherein the antistatic agent is carbon black; the stabilizer is calcium stearate; the antioxidant is antioxidant 1098; the flame retardant is magnesium hydroxide; and the coupling agent is silane coupling agent KH-560. Ordinary polyacrylamide is not contained. The dosage of the antistatic agent is increased.
[0044] To further verify the performance of the above materials, Examples 1-4 were prepared into nylon products under the following processing conditions:
[0045] The nylon 66, nano-polyacrylamide or ordinary polyacrylamide, antistatic agent, flame retardant, antioxidant, coupling agent, stabilizer and other raw materials of Examples 1-5 are put into a mixer according to the proportion and stirred and mixed, and extruded into granules in a twin-screw extruder, with a feeding section of 240°C, a compression section of 260°C, a homogenization section of 265°C, and a die of 270°C; the extrusion speed is 245r / min, and the feeding speed is 14r / min. Injection molding process conditions: feeding section 255°C, middle section 270°C, gate 270°C, to obtain nylon granules.
[0046] The surface resistance was tested according to the method in ASTM D257 standard; the cantilever beam notched impact strength was tested according to the method in ASTM D256 standard, the tensile strength was tested according to ASTM D638, and the heat deformation temperature was tested according to ASTM D648. The specific results are shown in Table 1.
[0047] Table 1 Performance test of products of Examples 1-4
[0048] Product Type Resistance / Ω Tensile strength / MPa <![CDATA[Impact strength kJ / m 2 > Heat Deflection Temperature Example 1 <![CDATA[6.7x10 7 ]]> 29.7 252 272 Example 2 <![CDATA[2.7x10 7 ]]> 28.3 249 275 Example 3 <![CDATA[8.2x10 8 ]]> 18.1 216 261 Example 4 <![CDATA[7.7x10 9 ]]> 11.2 192 235 Example 5 <![CDATA[3.4x10 8 ]]> 9.7 168 218
[0049] It can be seen from the above data that the nylon masterbatch with antistatic effect prepared in Example 1 and Example 2 has good antistatic properties and good mechanical properties, indicating that the performance of nano-polyacrylamide is relatively stable. Comparing Example 3 and Example 4, it can be seen that the various properties of polyacrylamide induced by SiO2 crystal seeds are better than those of ordinary polyacrylamide. This is because the polyacrylamide obtained by using SiO2 crystal seeds as core induction is nano-scale particle size, has good compatibility and dispersibility, can allow the components to give full play to their performance, and SiO2 can effectively increase the toughness of the material, improve heat resistance, and improve mechanical properties. The tensile strength, impact strength, and heat deformation temperature of Example 1 are all higher than those of Example 3 and Example 4. It should be noted that Example 5 adds more than double the amount of antistatic agent, and it does not have excellent antistatic properties of adding nano-polyacrylamide and a small amount of antistatic agent alone, indicating that the dispersion effect of nano-polyacrylamide on the antistatic agent is obvious, and the addition amount of the antistatic agent can be greatly reduced, thereby ensuring good mechanical properties.
Claims
1. An antistatic nylon material, characterized in that: The components include 70-85 parts of nylon, 10-20 parts of nano-polyacrylamide, 5-10 parts of antistatic agent, 10-15 parts of flame retardant, 1-2 parts of antioxidant, 1-2 parts of coupling agent, and 1-2 parts of stabilizer by weight; wherein the nano-polyacrylamide is a nano-polyacrylamide prepared by SiO2 seed crystals as nuclear induction; the preparation method of the nano-polyacrylamide specifically includes the following steps: S1, mixing fluorosilicic acid and ammonia water, and aging to obtain SiO2 seed solution; S2, dissolving the polymerization monomer and the surfactant in the seed solution obtained in step S1, and then adding an initiator to initiate a polymerization reaction to obtain a polymer aqueous solution; S3, adding a crystallizing agent to the polymer aqueous solution obtained in S2, the polymer is precipitated, the solid-liquid is separated, and the obtained solid is washed and dried to obtain nano-polyacrylamide.
2. The antistatic nylon material according to claim 1, characterized in that: The antistatic agent is carbon black; the flame retardant is magnesium hydroxide; and the antioxidant is any one of antioxidant 1010, antioxidant 1098 and antioxidant 168.
3. The antistatic nylon material according to claim 1, characterized in that: In step S2, the weight concentration ratio of the polymer to the seed crystal is 20-150:1; In step S2, the polymerization monomer is selected from two or more of acrylamide, methacrylamide, N-isopropylacrylamide and acrylic acid; in step S2, the surfactant is a sulfonic acid surfactant, and the amount of the surfactant is 0.1-2% by weight of the polymerization monomer.
4. The antistatic nylon material according to claim 1, characterized in that: The initiator is a redox initiator, and the amount of the initiator is 1-3% of the weight of the polymerization monomer.
5. An antistatic nylon material as claimed in claim 4, characterized in that: The redox initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium perbromide and hydrogen peroxide.
6. The antistatic nylon material according to claim 1, characterized in that: In step S1, the concentration of fluorosilicic acid is 3-10wt%, the concentration of ammonia water is 2-10%, the pH value at the mixing end point is controlled at 6-7, and the aging time is 1-12h.
7. The antistatic nylon material according to claim 1, characterized in that: In the step S3, the crystallization agent is an organic solvent that is soluble in water but does not dissolve the polymer product.
8. An antistatic nylon material as claimed in claim 7, characterized in that: The organic solvent is at least one of methanol, ethanol and acetone; the amount of the crystallizing agent is 10-60% of the total weight of the water in step S1.
9. The antistatic nylon material according to claim 1, characterized in that: The coupling agent is silane coupling agent KH-550 or KH-560; the stabilizer is any one of erucic acid amide and calcium stearate.
10. A method for preparing the antistatic nylon material according to claim 1, characterized in that: Put nylon, nano-polyacrylamide, antistatic agent, flame retardant, antioxidant, coupling agent, stabilizer into a mixer, stir and mix, extrude and granulate in a twin-screw extruder, feed section 230-250℃, compression section 260-270℃, homogenization section 265-270℃, die 270-275℃; extrusion speed 245r / min, feeding speed 14r / min. Injection molding process conditions: feed section 255℃, middle section 270℃, gate 270℃.
Citation Information
Patent Citations
Method for preparing polyacrylamide
CN103554320A
Flame-retardant heat-conduction anti-static nylon 66 composite material and preparation method thereof
CN104672897A
Mixed antistatic semi-aromatic nylon resin and preparation method thereof
CN111138847A
Preparation method of composite flame-retardant material
CN118667229A